Wind turbine ice detection using AEP loss method: A case study. Issue 4 (August 2022) - Jin, Jia Yi; Karlsson, Timo; Virk, Muhammad S
This paper describes the comparison of a statistical and numerical case study of wind resource assessment and estimation of resultant Annual Energy Production due to ice of a wind park in ice prone cold region. Three years Supervisory Control and Data Acquisition data from a wind park located in arctic region is used for this study. Statistical analysis shows that the relative power loss due to icing related stops is the main issue for this wind park. While Larsen wake model is used for the CFD simulations, where results show that it is important to use the wake loss model for CFD simulations of wind resource assessment and AEP estimation of a wind park. A preliminary case study about wind park layout optimization has also been carried out which shows that AEP can be improved by optimizing the wind park layout and CFD simulations can be a good tool.